SOME RECOMMENDATIONS FOR ADDITIONAL PROTECTION - Mishchenko, T. M. (Science and Transport Progress, 2007)
On the basis of theoretical research, it is offered to increase inductance of the shunting branch of tractive motor and also to use its switching-off before restoration of voltage on the current collector in the «removal−restoration» mode.